Analysis of interpersonal function in greta thunberg speech - Adystianto, Marvelia Pratama; Jayantini, I G A Sri Rwa; Suastini, Ni Wayan (Institut Pariwisata dan Bisnis Internasional, 2020)
The research aimed to discover the types of interpersonal functions and encourage awareness in a speech. This analysis was conducted using the qualitative method analysis with Greta Thunberg’s speech transcription in the United Nation Climate Action Summit as the subject of analysis. Then, the data were separated into the form of the clauses. The analysis was conducted based on Halliday's theory. The results of analysis showed that declarative sentences dominated Thunberg’s speech, then inclination modality and second personal pronoun “you” predominantly found in the speech. Thunberg also attempted to use the subject “I